Reliability of mortgage valuation for institutional lending in Nigeria - Aluko, Bioye Tajudeen (International Journal of Strategic Property Management, 2010)
The growing number of distressed banks in Nigeria and the recognition of mortgage valuation as a measure of investment performance of collaterals to mitigate the risks of loan underwriting process necessitates this study. It examined whether open market valuations of mortgage properties were a good proxies for their sale prices. Pooled data, involving 121 open market sales during the period 1994 to 2002, on property transactions in the study area with their corresponding contemporaneous valuations were gathered from the estate surveying and valuation firms, the lending institutions and the Nigerian Deposit Insurance Corporation. The data emanating therefrom were analysed with the aid of multiple regression models. The study revealed, amongst other things, that open market valuation for mortgage is a good proxy for their transaction price in the study area; although, the accuracy is not as good as what obtains in U.K, U.S.A. and Australia.First Published Online: 18 Oct 2010